Immune evasion in acute myeloid leukemia: current concepts and future directions. Issue 1 (27th August 2013) - Teague, Ryan M; Kline, Justin
Abstract : Immune responses generated against malignant cells have the potential to inhibit tumor growth, or even eliminate transformed cells before a tumor forms. However, immune tolerance mechanisms that normally protect healthy tissues from autoimmune damage pose a formidable barrier to the development of effective anti-tumor immunity. Because malignant cells are derived from self-tissues, the majority of defined tumor antigens are either shared or aberrantly expressed self-proteins. Eliciting productive T cell responses against such proteins is challenging, as most high-affinity, self-reactive T cells are purged during thymic selection. Some T cells capable of tumor antigen recognition escape thymic deletion, but are functionally inhibited by peripheral tolerance mechanisms which limit their ability to attack a developing malignancy. Alternatively, some tumors express antigens derived from mutated self-proteins, viral proteins or self proteins expressed only during embryonic development. These antigens are recognized by the immune system as foreign and could be recognized by a relatively large number of peripheral T cells. Even in this scenario, tumors evade otherwise effective T cell responses by employing potent immunosuppressive mechanisms within their local environment. In the setting for solid malignancies, such as melanoma, a growing number of putative immune evasion mechanisms have been characterized. However, acute myeloid leukemia (AML) is a systemic disease, and the pathways it exploits to subvert the host immune response may be quite different than those of a solid tumor. Much remains unknown regarding the immune escape mechanisms promoted by AML, and whether efforts to thwart tolerance may influence the progression of this disease. Here, we review current concepts of immune evasion in AML, and speculate how potentially effective immunotherapeutic strategies might be developed to reverse immune tolerance in leukemia patients in the future.